Dietary artemisinin boosts intestinal immunity and healthy in fat greenling (Hexagrammos otakii) - Gu, Yixin; Wang, Wenjie; Zhan, Yu; Wei, Xiaoyan; Shi, Yanyan; Cui, Dandan; Peng, Tingting; Han, Jian; Li, Xuejie; Chen, Yan; Xue, Zhuang; Wang, Wei (Frontiers in Immunology, 2023)
Introduction Artemisinin (ART) is very common as a diet additive due to its immunoregulatory activities. Nonetheless, the immunoregulatory mechanism of ART in marine fish remains unknown. This study comprehensively examined the effects and explored the potential mechanism of ART ameliorating intestinal immune disease (IID) in fat greenlings (Hexagrammos otakii). Methods and results The targets of ART were screened using the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Here, eight putative targets of ART were collected and identified with the Uniprot database, and 1419 IID-associated target proteins were filtered through the Drugbank, Genecards, OMIM, and PHARMGKB Databases. The results of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways point out that ART may have immunoprotective effects by regulating cellular responses to stress, hypoxia, inflammation, and vascular endothelial growth factor stimulus through the hypoxia-inducible factor 1 (HIF-1) signaling pathway. The findings of molecular docking indicated that ART contains one active ingredient and three cross-targets, which showed a kind combination with hypoxia-inducible factor 1-alpha (HIF1-a), transcription factor p65 (RELA), and vascular endothelial growth factor A (VEGF-A), respectively. Furthermore, an ART feeding model was established to assess the ART’s immunoprotect effect on the intestine of H.otakii in vivo. The D48 group showed smaller intestinal structural changes after being challenged by Edwardsiella tarda. The supplementation of ART to the diet improved total superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) and reduced the malondialdehyde (MDA) in intestine of H. otakii. The expression of transcription factor p65, HIF1-α, VEGF-A, cyclin D1, matrix metalloprotease 9 (MMP9), monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6) was decreased after dietary ART in the intestinal of H. otakii. Discussion The present results demonstrated that dietary ART improved antioxidants and immunity, optimized the intestinal structure, and increased resistance to E. tarda through the SOD2/nuclear-factor-kappa- B (NFkB)/HIF1-a/VEGF-A pathway in the intestinal tract of H.otakii. This study integrated pharmacological analysis and experimental validation and revealed the mechanism of ART on IID, which provides insight into the improvement of IID in H. otakii.